2016
DOI: 10.1002/cbic.201500613
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Activated Reversible Imine Isomerization: Towards a Photochromic Protein Switch

Abstract: Mutants of cellular retinoic acid-binding protein II (CRABPII), engineered to bind all-trans-retinal as an iminium species, demonstrate photochromism upon irradiation with light at different wavelengths. UV light irradiation populates the cis-imine geometry, which has a high pKa, leading to protonation of the imine and subsequent “turn-on” of color. Yellow light irradiation yields the trans-imine isomer, which has a depressed pKa, leading to loss of color because the imine is not protonated. The protein-bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The significant red shifts for these bands for Fc-den (294 nm, 362 nm) in comparison to the starting materials 1 (262 nm, 330 nm) and 2 (266 nm, 338 nm) were ascribed to the π-conjugation within the dendrimer framework. A significantly smaller peak at 488 nm for Fc-den (observed only for this compound) could be attributed to the dynamic E-Z isomerization behavior within imine-type linkages 25 or some metal-to-triphenylbenzene charge transfers 26 . Fc and its derivatives easily undergo one electron oxidation to form ferrocenium cation in a reversible manner.…”
Section: Dalton Transactions Accepted Manuscriptmentioning
confidence: 82%
“…The significant red shifts for these bands for Fc-den (294 nm, 362 nm) in comparison to the starting materials 1 (262 nm, 330 nm) and 2 (266 nm, 338 nm) were ascribed to the π-conjugation within the dendrimer framework. A significantly smaller peak at 488 nm for Fc-den (observed only for this compound) could be attributed to the dynamic E-Z isomerization behavior within imine-type linkages 25 or some metal-to-triphenylbenzene charge transfers 26 . Fc and its derivatives easily undergo one electron oxidation to form ferrocenium cation in a reversible manner.…”
Section: Dalton Transactions Accepted Manuscriptmentioning
confidence: 82%
“…The study of organic semiconductor compounds with photochromic properties is of great significance [ 1 ] in the manufacture of devices such as antireflective systems for screens [ 2 ], optical memory systems [ 3 ], optical switches [ 4 , 5 , 6 ], OFETs (Organic Field Effect Transistor) [ 7 , 8 ], smart windows [ 9 ] and a wide variety of sensors [ 10 , 11 , 12 ]. It has been shown that the photochromic response of organic materials depends on the functional groups type and on the molecule structure [ 1 , 13 , 14 , 15 , 16 ]. In previous studies, we reported on the reversible photochromic effect of imine-type materials, and we also reported on the type of terminal functional groups, as well as the synthesis method influencing these properties.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we reported on the reversible photochromic effect of imine-type materials, and we also reported on the type of terminal functional groups, as well as the synthesis method influencing these properties. [ 15 , 16 , 17 , 18 ]. A change in color is observed when imine type compounds were irradiated with sunlight; interestingly, the original color is recovered if the compound is placed in dark conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Not only has a faster maturing system operational advantages, enabling the researcher to carry out experiments without delay, but also and more consequentially, a fast‐reacting mutant outcompetes the off‐target imine formation that leads to potential background issues. Mutational hotspots discovered previously to enhance the rate of iminium formation for binding all‐ trans ‐retinal and merocyanine aldehyde (MRCA) were tested with JRA . The most effective mutations were A33W, T29L, T53C, and R58W.…”
Section: Resultsmentioning
confidence: 99%